2013
DOI: 10.1179/1973947813y.0000000071
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of acute tonsillopharyngitis in primary care: a new approach for low-resource settings

Abstract: Centor criteria could be safely used to reduce unnecessary antibiotic usage for tonsillopharyngitis in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 24 publications
0
12
0
7
Order By: Relevance
“…The searches identified 80 citations. The full selection process (outlined in Figure 1) resulted in 18 studies 2,6,11,12,[24][25][26][27][28][29][30][31][32][33][34][35][36][37] being included in the review; 10 of these used the Centor score 2,11,12,[24][25][26][27][28][29][30][31] and eight used the McIsaac score. 6,11,12,[32][33][34][35][36][37] Only one study -reported by Fine et al 11,12 -provided sufficient data to allow a direct comparison between the two tests.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The searches identified 80 citations. The full selection process (outlined in Figure 1) resulted in 18 studies 2,6,11,12,[24][25][26][27][28][29][30][31][32][33][34][35][36][37] being included in the review; 10 of these used the Centor score 2,11,12,[24][25][26][27][28][29][30][31] and eight used the McIsaac score. 6,11,12,[32][33][34][35][36][37] Only one study -reported by Fine et al 11,12 -provided sufficient data to allow a direct comparison between the two tests.…”
Section: Study Selectionmentioning
confidence: 99%
“…Full study characteristics are detailed in Table 1. Of those studies using the Centor score, eight were conducted in Europe 2, [24][25][26][27][29][30][31] and two in the US. 11,12,28 Of those studies using the McIsaac score, three were conducted in Europe, 32,33,36 four in North America, 6,11,12,35,37 and one in Australia.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…"Sore throat" symptoms, including pharyngitis, are common reasons for seeking medical assistance in primary care and emergency services,1 accounting for 12 million consultations a year in the United States in 2006, with a significant impact to the healthcare system 23…”
mentioning
confidence: 99%
“…Os sintomas "dor de garganta", incluindo as faringites, são causas comuns de procura do atendimento médico nos serviços de atenção primária e de urgência,1 sendo responsáveis nos Estados Unidos por 12 milhões de atendimentos ao ano, em 2006, com importante impacto para o sistema de saúde 2. Embora a maioria dos casos de faringites seja de etiologia viral (50-80%), as bactérias estão implicadas em cerca de 5-30% dos casos 3…”
unclassified
See 1 more Smart Citation